IMPLEMENTASI KEBIJAKAN MONETER DI INDONESIA (Fokus Ekonomi, 2008)
Monetary policy is a main policy used by Bank Indonesia for the stabilization of macro economy. Monetary policy instruments include: an open market policy, the discount policy and reserve reqiirement.. In the implementation experience obstacles for policy makers related with trade off between the final target, other beside it there is uncertainly condition caused the achievement of the ultimate goal is not achieved. Therefore we need an operational target (interest rate) as a target of achieving the ultimate goal (inflation). Key words: monetary policy, operational goals, end goals